Face-to-face education with a virtual support: an experience of Honduras on COVID-19 times - Acosta Álvarez, Celio Luis (2020)
The aim of this research has been to reveal the educational proposal carried out by one of Honduras universities to virtualize its processes during COVID-19 and to determine the satisfaction of professors and students regarding the proposal. This research, under an exploratory and non-experimental descriptive design, had two phases: reconstruction of the experience and a satisfaction study using a Likert-5 point scale tool carried out to a sample n = 1156 students and n =130 professors. The results have allowed to identify three transition stages to virtualization: ensuring, reorganizing and implementing; to define face-to-face education with a virtual support as the modality study applied, and to verify a high level of satisfaction of students and professors. The results allow the transition and development of a face-to-face education with a virtual support modality as an alternative to the virtualization of educational processes in higher education.